THE ROLE OF DIGITALIZATION IN FORMATION THE FINANCIAL AND ECONOMIC SECURITY OF AN ENTERPRISE - Гаврікова, Аліна; Свинаренко, Тетяна; Самодрига, Яна (SWorldJournal, 2025)
The article explores the essence of an enterprise’s financial and economic security, emphasizing its dynamic nature shaped by internal and external environmental factors. It highlights the development scenarios of digital transformation in Ukraine during